Tax Loss Carrybacks: Investment Stimulus versus Misallocation - Bethmann, Inga; Jacob, Martin; Müller, Maximilian A. (The Accounting Review, 2018)
ABSTRACT Tax regimes treat losses and profits asymmetrically when profits are immediately taxed, but losses are not immediately refunded. We find that treating losses less asymmetrically by granting refunds less restrictively increases loss firms' investment: A third of the refund is invested and the rest is held as cash or returned to shareholders. However, the investment response is driven primarily by firms prone to engage in risky overinvestment. Consistent with the risk of misallocation, we find a delayed exit of low-productivity loss firms receiving less restrictive refunds, indicating potential distortion of the competitive selection of firms. This distortion also negatively affects aggregate output and productivity. Our results suggest that stimulating loss firms' investment with refunds unconditional on their future prospects comes at the risk of misallocation. JEL Classifications: G31; H21; H25.